Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1007/s00066-004-9193-0
|View full text |Cite
|
Sign up to set email alerts
|

Internal Mammary Nodes in Invasive Breast Carcinoma

Abstract: Consistent literature data exist indicating a diminished survival in patients with inner versus outer quadrant breast cancer. According to our data, RT with a total dose of 50 Gy to IMNs in breast cancer patients with medial lesions was associated with OS and SDFS rates comparable to patients with lateral tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
(42 reference statements)
1
18
0
2
Order By: Relevance
“…Some studies suggested no survival differences attributable to IMN treatment [12,26]. Others series reported rare recurrences when the IMN were treated, either by surgery [53] or radiotherapy [36], and that survival may be improved with IMN irradiation [13,19,56]. Randomized trials of extended mastectomy removing the IMN and randomized trials of radiotherapy targeting the IMN have not demonstrated significant effect of IMN treatments on survival [16,22].…”
mentioning
confidence: 99%
“…Some studies suggested no survival differences attributable to IMN treatment [12,26]. Others series reported rare recurrences when the IMN were treated, either by surgery [53] or radiotherapy [36], and that survival may be improved with IMN irradiation [13,19,56]. Randomized trials of extended mastectomy removing the IMN and randomized trials of radiotherapy targeting the IMN have not demonstrated significant effect of IMN treatments on survival [16,22].…”
mentioning
confidence: 99%
“…Despite the high positive rate, the dissection of IML nodes has not been taken seriously since the application of modified radical mastectomy in breast cancer treatment [24]. It was not until recent years, after the development of sentinel lymph node biopsy [37,38,39] and the application of lymphoscintigraphy [40] and thoracoscopic technology [41], that the importance of the IML nodes was again recognized [42,43]. In our analysis, the positive rate of IML nodes was high (23%), suggesting that knowing the status of the IML nodes is essential for accurate tumor staging and for the selection of appropriate chemotherapy and radiotherapy to improve the patients' survival.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no general agreement on the necessity of regional nodal irradiation (RNI) [6,7,18,19]. Until recently, there has been limited information with regard to locoregional and distant failure rates for breast cancer patients (one to three positive nodes) with or without extracapsular extension (ECE) and the decision to routinely use nodal fields in ECE-positive patients remains a controversial one [19,23].…”
Section: Introductionmentioning
confidence: 99%